2=11+3m(m+3)

Simple and best practice solution for 2=11+3m(m+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=11+3m(m+3) equation:



2=11+3m(m+3)
We move all terms to the left:
2-(11+3m(m+3))=0
We calculate terms in parentheses: -(11+3m(m+3)), so:
11+3m(m+3)
determiningTheFunctionDomain 3m(m+3)+11
We multiply parentheses
3m^2+9m+11
Back to the equation:
-(3m^2+9m+11)
We get rid of parentheses
-3m^2-9m-11+2=0
We add all the numbers together, and all the variables
-3m^2-9m-9=0
a = -3; b = -9; c = -9;
Δ = b2-4ac
Δ = -92-4·(-3)·(-9)
Δ = -27
Delta is less than zero, so there is no solution for the equation

See similar equations:

| 4x+1=-2x+37 | | 18=-35+x | | 819=-21w | | v+18=17 | | -9(x-4)-6=x | | -2n+9/8=211/40 | | 2(t+1)=6t-1 | | 64=6+s | | 13=y+16 | | 8r=3-4(4) | | 1-2)2x+7-5x+8=3(5+6x)-12x | | b-66=20 | | 4x-2(x-3)=-8+5x-3 | | 4.83=-4.72-z | | 4x+11=-2x+37 | | -2n+11/8=511/40 | | l-18=-6 | | 4/6Xa-1/6=2/6 | | 52=t/3+42 | | t-9=48 | | 13=j/17 | | .–2.3f=9.2 | | j+2=5 | | z-36=6 | | 5=-25x+15 | | 4(3)(-x)=12 | | 3c+-3=6 | | -3.4=2.8x-0.8x | | t-17=68 | | 10x-2=-42 | | 14=q/22 | | 82=u+67 |

Equations solver categories